Decree of the President of the Arab Republic of Egypt No. 647 of the Year 2017 = قرار رئيس جمهورية مصر العربية رقم 647 لسنة 2017 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic